Inkunabuł w oprawie z superekslibrisami bpa Jana Lubrańskiego na tle introligatorstwa krakowskiego i poznańskiego końca XV – początku XVI wieku - Wagner, Arkadiusz (Archiwa, Biblioteki i Muzea Kościelne, 2021)
The article focuses on the binding of the incunabulum from the book collection of one of the greatest Polish Renaissance bibliophiles, Jan Lubrański Bishop of Poznań. The great value of this historical monument, discovered in 2012 in the Library of the Seminary in Włocławek, results from the fact that it is one of the few volumes that remained from hierarch’s extensive book collection, and also the only one, so far discovered, marked with his supralibros. The article starts with a biographical outline of Bishop Lubrański, with special attention paid to his bibliophilic activity. Then, the author presents a detailed formal and stylistic analysis of the binding against the background of bookbinding of the Polish leading centers in this fi eld in the late fi fteenth and sixteenth centuries. The result is the hypotheses concerning the time and place of its creation, which point to the unknown bookbinding workshop in Cracow or Poznań, operating in the fi rst two decades of the sixteenth century. Finally, the author attempts to trace the history of the book from the time of Lubrański up to its discovery in the collections of Włocławek.